Value for Money Analysis on the Electricity Management Program of the East Nusa Tenggara Province Energy and Mineral Resources Office - Hans, Yohanes Aquino Alfredo; Man, Stanis; Suninono, Alfonsus Rodriques (Global Education Journal, 2025)
Public sector organizations are currently often considered by the public as less than optimal, less productive, low quality of performance, and a source of waste of funds. The purpose of the research is to find out and measure financial performance using the Value for money method at the Energy and Mineral Resources Office of East Nusa Tenggara Province in 2023. This study uses qualitative and quantitative descriptive methods (Mixed Research), with data collection techniques through interviews, observations, and documentation. The data obtained is systematically analyzed to understand the extent to which the principle of Value for money is applied in the budget management of the electricity management program. The results of the study show that the Economic Ratio of the Electricity Management Program at the Energy and Mineral Resources Office of East Nusa Tenggara Province in 2023 is relatively economical, with a ratio achievement of 124%, which reflects economical budget management and in accordance with the principle of value for money. However, the efficiency ratio shows that most of the activities in the program are still classified as inefficient, with many activities having an efficiency achievement of 0%, indicating that the use of the budget is not optimal in producing the expected output.